Leadership and Crew Resource Management in High-Reliability Organizations: A Competency Framework for Measuring Behaviors. Issue 2 (3rd April 2017) - Alavosius, Mark P.; Houmanfar, Ramona A.; Anbro, Steven J.; Burleigh, Kenneth; Hebein, Christopher
ABSTRACT: High-reliability organizations (HROs) have emerged across a number of highly technical, and increasingly automated industries (e.g., aviation, medicine, nuclear power, and oil field services). HROs incorporate complex systems with a large number of employees working in dynamic, and potentially dangerous environments. Effectively managing contingencies in HROs, to simultaneously promote safe and efficient behaviors is a daunting task. Crew Resource Management (CRM) has emerged in HROs as a highly effective approach to training and sustaining essential skills within work teams operating across a large workforce. CRM provides a competency framework that enables adherence to standard work instructions while, at the same time, encourages adaptive variance in responding to effectively manage current environmental circumstances that depart from normal routines. This paper considers the development of CRM across several high-reliability industries, develops a behavior analytic account of CRM behaviors, and describes an approach to measuring behaviors within simulated and actual work environments.